1998
DOI: 10.1002/(sici)1096-8628(19981002)79:4<274::aid-ajmg8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hemihyperplasia (hemihypertrophy): Report of a prospective multicenter study of the incidence of neoplasia and review

Abstract: Hemihyperplasia is characterized by asymmetric growth of cranium, face, trunk, limbs, and/or digits, with or without visceral involvement. It may be an isolated finding in an otherwise normal individual, or it may occur in several syndromes. Although isolated hemihyperplasia (IHH) is of unknown cause, it may represent one end of the clinical spectrum of the Wiedemann-Beckwith syndrome (WBS). Uniparental paternal disomy of 11p15.5 or altered expression of insulin-like growth factor 2 (IGF2) from the normally si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
119
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 37 publications
3
119
0
2
Order By: Relevance
“…Clinically, it has to be distinguished from other overgrowth syndromes (OGS) such as Simpson ± Golabi ± Behmel syndrome and it must also be recognised in its incomplete or related forms such as nonsyndromic IGF2 overgrowth disorder 4 and isolated hemihyperplasia. 5 Molecular diagnosis is also difficult, mostly because of the large spectrum of genetic and epigenetic abnormalities. Current molecular tests allow diagnosis of BWS in only one third of patients: rare patients with cytogenetic abnormalities, 20% of patients with 11p15 UPD, 8% of patients with hypermethylation of the H19 gene and 5% of patients with a mutation in CDKN1C.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it has to be distinguished from other overgrowth syndromes (OGS) such as Simpson ± Golabi ± Behmel syndrome and it must also be recognised in its incomplete or related forms such as nonsyndromic IGF2 overgrowth disorder 4 and isolated hemihyperplasia. 5 Molecular diagnosis is also difficult, mostly because of the large spectrum of genetic and epigenetic abnormalities. Current molecular tests allow diagnosis of BWS in only one third of patients: rare patients with cytogenetic abnormalities, 20% of patients with 11p15 UPD, 8% of patients with hypermethylation of the H19 gene and 5% of patients with a mutation in CDKN1C.…”
Section: Introductionmentioning
confidence: 99%
“…İHH'li çocuklarda ortalama yaşam süresi beklenebilmekle birlikte eşlik eden anomaliler uzun dönem prognozunu değiş-tirebilmektedir. 4 Sıklıkla sporadik olarak görülse de ailesel geçiş de tanımlanmıştır. 2 Olgumuzun aile öyküsünde benzer sendromların olmaması ve diğer eşlik eden bulguların yokluğu nedeniyle hastamız sporadik, izole basit hemihipertrofi olarak değerlendirildi.…”
Section: Discussionunclassified
“…The asymmetry can be due to differences in the growth of soft tissue, bone, or both [2] Hemihyperplasia may be an isolated finding, or it may be part of multiple malformation syndromes, such as Russell-Silver syndrome, Proteus syndrome, Beckwith-Wiedemann Syndrome (BWS), and Sotos syndrome [3,4]. Isolated hemihyperplasia (IH, OMIM 235000) is defined as asymmetric regional body overgrowth due to an underlying abnormality of cell proliferation without any other underlying diagnosis [5]. Rowe [6] proposed a classification system for hemihyperplasia, based on anatomic site of involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of IH is unknown. A number of different chromosomal anomalies, including trisomy [7] mosaicism and diploidtriploid mosaicism, have been identified, and the causes of IH are likely to be heterogeneous [5]. It has been suggested that IH could be one end of the spectrum of phenotypes of BWS [8], linked to the chromosomal locus 11p15 [9].…”
Section: Introductionmentioning
confidence: 99%